2005
DOI: 10.1093/toxsci/kfj062
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicology of Ligands for Peroxisome Proliferator-Activated Receptors (PPAR)

Abstract: Peroxisome proliferator-activated receptors (PPARs) are ligand activated transcription factors that modulate target gene expression in response to endogenous and exogenous ligands. Ligands for the PPARs have been widely developed for the treatment of various diseases including dyslipidemias and diabetes. While targeting selective receptor activation is an established therapeutic approach for the treatment of various diseases, a variety of toxicities are known to occur in response to ligand administration. Whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
167
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(171 citation statements)
references
References 303 publications
3
167
0
1
Order By: Relevance
“…As a nuclear receptor involved in multiple physiological regulations (Cheng et al, 2004;Kim et al, 2004;Piqueras et al, 2007), PPAR-b is an ideal drug target for the treatment of diseases. Studies have shown a wide range of PPAR-b agonists, including eicosanoids, fatty acids and some synthetic compounds (for example, GW501516); GW501516 is currently in a phase II clinical trial for dyslipidemia (Barish et al, 2006;Peraza et al, 2006;Takahashi et al, 2006). Because of its protective role in the carcinogenesis and progression of colon cancer as suggested in this study, PPAR-b may be a potential drug target for colon cancer.…”
Section: Studies Have Identified Ilk As a Direct Target Of Ppar-b (mentioning
confidence: 82%
“…As a nuclear receptor involved in multiple physiological regulations (Cheng et al, 2004;Kim et al, 2004;Piqueras et al, 2007), PPAR-b is an ideal drug target for the treatment of diseases. Studies have shown a wide range of PPAR-b agonists, including eicosanoids, fatty acids and some synthetic compounds (for example, GW501516); GW501516 is currently in a phase II clinical trial for dyslipidemia (Barish et al, 2006;Peraza et al, 2006;Takahashi et al, 2006). Because of its protective role in the carcinogenesis and progression of colon cancer as suggested in this study, PPAR-b may be a potential drug target for colon cancer.…”
Section: Studies Have Identified Ilk As a Direct Target Of Ppar-b (mentioning
confidence: 82%
“…Ligands for PPARs exhibit potent anti-inflammatory effects related to innate and adaptive immunity in various disease models, including IBD and EAE. However, use of PPAR ligands as therapeutics is limited by their adverse side effects (Peraza et al, 2006). Combinations of PPAR and RXR agonists may produce synergistic effects with reduced side effects .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to transcriptionally-mediate events, ligands for PPARs can also cause changes in the phosphorylation of proteins that can also modulate cell cycle, and these events can be mediated by both receptor-dependent and receptor-independent mechanisms (reviewed in [40]). To begin to examine the changes in phosphorylation-dependent signaling, global analysis of phosphorylated cell cycle proteins was performed using the Kinexus KPSS 10.0 Screen.…”
Section: Gw0742 Inhibits Mapk Signaling In N/tert-1 Keratinocytesmentioning
confidence: 99%